If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -9x + 11 = -288 Reorder the terms: 11 + -4x + -9x = -288 Combine like terms: -4x + -9x = -13x 11 + -13x = -288 Solving 11 + -13x = -288 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -13x = -288 + -11 Combine like terms: 11 + -11 = 0 0 + -13x = -288 + -11 -13x = -288 + -11 Combine like terms: -288 + -11 = -299 -13x = -299 Divide each side by '-13'. x = 23 Simplifying x = 23
| 5(2x-2)+53=7x-8 | | 249/843 | | -7x+15=-3x+35 | | 714y-6=799*98784 | | 111*d=12321 | | 3x+(x-30)=180 | | 1/3x-18=x-6 | | 8c^2-8c= | | 27=4-2x+3 | | 4(2x-3)=2(3x-8) | | 2x+x+12=90 | | x^3/4(x^1/2)^3/2 | | f(x)=5x^2+100x+504 | | -6x-7=3x-2 | | 5.2-X=-18.73 | | 2(-x+6)=10x-3 | | 80x+10(1.5x)=1730.77 | | -4n-8=-12+8 | | 11(k-1)=7(k-10) | | 3w=1/9 | | 78-u=172 | | 2x+4(-5x+14)=-70 | | 2b+15=-b-3b+5b | | 80x+10(1.5x)=45000 | | 2/7*A=B*(3/10)*(4/9) | | 3(x-2)+1=3+x | | 3x^2+9x=8 | | 4x=10+4x-5 | | 4p-5+p=75p+2 | | 7+1.25x=43.25 | | 9x+16=15x-8 | | 5(l-4)=3(1+2) |